2016
DOI: 10.1038/nprot.2016.016
|View full text |Cite|
|
Sign up to set email alerts
|

Isolation and cultivation of naive-like human pluripotent stem cells based on HERVH expression

Abstract: The ability to derive and stably maintain ground-state human pluripotent stem cells (hPSCs) that resemble the cells seen in vivo in the inner cell mass has the potential to be an invaluable tool for researchers developing stem cell-based therapies. To date, derivation of human naive-like pluripotent stem cell lines has been limited to a small number of lineages, and their long-term culturing remains problematic. We describe a protocol for genetic and phenotypic tagging, selecting and maintaining naive-like hPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…RNA-seq data in human embryonic and pluripotent stem cells revealed similar trends, where the HERVH subfamily is highly expressed and marked with the active promoter and enhancer chromatin marks (Wang et al 2016). Furthermore, a recent single-cell RNA-seq study also revealed the higher expression of ERVs at various stages of preimplantation embryogenesis in human and showed their ability to distinguish all cell-specific stages using TE transcription alone (Göke et al 2015).…”
Section: Introductionmentioning
confidence: 85%
“…RNA-seq data in human embryonic and pluripotent stem cells revealed similar trends, where the HERVH subfamily is highly expressed and marked with the active promoter and enhancer chromatin marks (Wang et al 2016). Furthermore, a recent single-cell RNA-seq study also revealed the higher expression of ERVs at various stages of preimplantation embryogenesis in human and showed their ability to distinguish all cell-specific stages using TE transcription alone (Göke et al 2015).…”
Section: Introductionmentioning
confidence: 85%
“…When isolated using cell sorting, HERVH‐GFP ‐high cells adopt a naïve‐like morphology compared to HERVH‐GFP ‐low/negative cells. Nonetheless, repeated re‐sorting is required to maintain a homogeneous population of naïve‐like hPSCs . The cell phenotype is also unclear given that endogenous HERVH transcription is associated with primed, and not with naïve, hPSCs …”
Section: Developing Methods To Identify and Isolate Naïve Hpscsmentioning
confidence: 99%
“…We also used 25 individual HERVs that represent each family for the enrichment analysis (Table 1). Most of the HERVs were found to be expressed HERV elements in previous reports [5156]. HERVs and disease conditions were considered as associated events when Fisher’s exact p-value was <0.001 and the odds ratio was >1.…”
Section: Methodsmentioning
confidence: 99%